ACCELERATING STUDENT COMPETENCY IN ENGLISH THROUGH EFFECTIVE LEARNING MANAGEMENT: INSIGHTS FROM MAN 2 MATARAM - Zuhratul Iman (UIN Sunan Gunung Djati Bandung, 2024)
This study examines the implementation of an English learning management system aimed at accelerating student competency at MAN 2 Mataram. This study analyzes aspects of planning, organizing, implementing, and controlling in the English learning process in an accelerated program tailored for language track students. Using a qualitative approach, data were collected through observation, interviews, and document analysis at MAN 2 Mataram, a leading Islamic high school in Mataram. The findings indicate that effective planning and organizing are essential to adapting the curriculum to the needs of diverse students, especially those with high cognitive abilities. The English curriculum is tailored to emphasize essential materials, allowing students to learn in an accelerated manner without being distracted by less relevant content. The implementation is supported by motivated and well-trained teachers, who use a variety of teaching methods to encourage active learning. However, this study identified several challenges, including limited resources and varying levels of student readiness, which were addressed through targeted interventions and continuous teacher supervision. This study concludes that a well-managed learning system, supported by a strong curriculum and effective teaching strategies, can significantly improve students' competency in English, especially in an accelerated learning environment. These findings provide valuable insights for educators and policy makers aiming to improve educational outcomes in similar contexts.